1991
DOI: 10.1161/01.hyp.18.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanism of endothelin-1 release by angiotensin and vasopressin.

Abstract: Release of endothelin-1, a novel potent vasoconstrictor peptide originally isolated from endothelial cells, from cultured bovine endothelial cells has been shown to be stimulated by arginine vasopressin and angiotensin II. To elucidate the cellular mechanism by which endothelin-1 is released by these vasoconstrictors, we tested the effects of several compounds on the agonist-induced endothelin-1 release and studied the changes of cytosolic free Ca peptide with 21-amino acid residues, was originally isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(112 citation statements)
references
References 18 publications
11
95
0
6
Order By: Relevance
“…10 Ang II induces vascular smooth muscle contraction through increasing cytosolic calcium 11 and also it facilitates the secretion of ET-1. 12 Growth hormone (GH) influences the growth and activity of different tissues. It influences the synthesis of insulin-like growth factor I (IGF-1).…”
Section: Introductionmentioning
confidence: 99%
“…10 Ang II induces vascular smooth muscle contraction through increasing cytosolic calcium 11 and also it facilitates the secretion of ET-1. 12 Growth hormone (GH) influences the growth and activity of different tissues. It influences the synthesis of insulin-like growth factor I (IGF-1).…”
Section: Introductionmentioning
confidence: 99%
“…18 In vitro studies have shown that AVP stimulates ppET-1 mRNA expression, 19 and a close correlation has also been reported between AVP plasma levels and urinary ET-1 excretion in volumedepleted exercising healthy subjects. 16 However, stepwise regression analysis revealed that in patients with HF, ANP, BNP, or AVP plasma concentrations were not independently related with urinary ET-1 excretion.…”
Section: Factors Possibly Responsible For Increased Renal Et-1 Producmentioning
confidence: 73%
“…Angiotensin II has been found to induce ppET-1 mRNA expression and the secretion of mature ET-1 in a dose-dependent manner in cultured bovine, rat, and human endothelial cells. 19 However, although the increased urinary ET-1 excretion observed in normal subjects on a low sodium diet paralleled PRA, ACE inhibition reduced ET-1 excretion by only 20%, 9 thus indicating that in this physiologic setting renal ET-1 formation is largely independent of the RAS. In NYHA class II patients urinary ET-1 excretion was increased despite the absence of PRA increase (Table II).…”
Section: Factors Possibly Responsible For Increased Renal Et-1 Producmentioning
confidence: 99%
“…Increased mRNA levels have been observed after treatment of the cells with growth factors and cytokines such as thrombin (13), transforming growth factor (TGF)-r3 (14), tumor necrosis factor (TNF)-a (15), interleukin (IL)-1 (16) and insulin, or with vasoactive substances (17,18) such as norepinephrine, angiotensin II, vasopressin, bradykinin, oxidized or acetylated low density lipoprotein (LDL). The increase in expression of endothelin-1 mRNA induced by thrombin, angiotensin II, and vasopressin has been shown to be promoted by an increase in intracellular Ca 2+ concentration and activation of protein kinase C (PKC) via GTP-binding protein following stimulation of their receptors (13,19). However, the mechanisms of regulation of mRNA expression by other substances remain to be elucidated.…”
Section: -1 Endothelin Gene and Regulation Of Its Expressionmentioning
confidence: 99%
“…After more than six years, the cloning and characterization of ECE have finally been successfully achieved. ECE is considered to be a potential target for selectively interrupting the biosynthesis of endothelin; although this approach has proven to be extremely difficult, an N-and C-terminaltruncated analogue of big endothelin-1 , [Phe22] big endothelin-1 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], was recently shown to be a potent inhibitor of ECE-1, being at least 30-fold more potent that phosphoramidon in blocking big endothelin-linduced vasoconstriction in the kidney (38).…”
Section: -1 Endothelin Gene and Regulation Of Its Expressionmentioning
confidence: 99%